Efficacy of Continuous Care Model Implementation on Body Mass Index and Lifestyle of Middle-aged Obese People - Mitra Tavakolizadeh; Mahdi Moshki; Mahdi Basiri Moghadam; Ali Delshad (Gonabad University of Medical Sciences, 2021)
Background: The aim of this study was to determine the effect of continuous care model application on body mass index (BMI) and lifestyle of middle-aged obese. Methods: 105 obese middle-aged were selected and assigned randomly to two groups. The data were collected using a meter, scale, and Walker health promotion lifestyle questionnaire (HPLP II). participants completed the questionnaire before undergoing the intervention, one, two, and three months after the intervention. Results: There was no significant difference between the experimental and control groups before the intervention considering all of the studied variables. However, a significant difference was observed between groups after the intervention in terms of lifestyle dimensions and obesity control performance. Conclusion: Considering the results of current study, the continuous care model can be effective for improving the lifestyle and health of middle-aged obese. Therefore, this model is recommended as a framework to design an overweight and obesity prevention plan.